Students’ Strategies in Learning English - Dara Jelita; Nuzulul Isna (Universitas Islam Negeri Palopo, 2025)
English is an international language that is essential to master, especially in terms of speaking skills. However, many students still face limited vocabulary, pronunciation difficulties, and a lack of confidence. This study, conducted in Aceh Barat Daya, Indonesia, explores students' strategies for improving their English-speaking proficiency using a qualitative case study approach. A total of 9 junior high school students (ages 13–15) from three schools were selected through purposive sampling based on their English proficiency, participation in academic activities, and additional learning experiences. Data were collected through in-depth interviews and documentation. The findings indicate that students employ a range of strategies to enhance their speaking skills, with learning and practice strategies being the most prevalent. The strategies employed include direct strategies (reading, looking for pronunciation, practicing, listening, and using English applications) and indirect strategies (using social media, structured lessons, self-directed learning, making friends with foreigners, and asking teachers and peers). The study recommends that teachers integrate these varied strategies into classroom instruction and promote technology-assisted speaking practice to better support students' development.